PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN PENGETAHUAN KONSEP DAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK DI SMK SWASTA GKPS1 PEMATANG RAYA KABUPATEN SIMALUNGUN: - - Saragih, Natanael; Sipayung, Rohdearni Wati; Damanik, Indra Jayanti; Purba, Benarita (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2024)
This abstract discusses the application of the Problem Based Learning (PBL) learning model at the GKPS1 Pematang Raya Private Vocational School, with the main aim of increasing students' conceptual knowledge and creative thinking abilities. The methods applied include problem orientation, organizing students, guiding investigations, developing work results, and assessment. The results of implementing PBL show a significant increase in student engagement in learning and their critical thinking abilities. The conclusion from this activity is that PBL is effective in creating meaningful learning experiences for students.